ESTIMATING SHAPE CORRESPONDENCE FOR POPULATIONS OF OBJECTS WITH COMPLEX TOPOLOGY - Fishbaugh, James; Pascal, Laura; Fischer, Luke; Tung Nguyen; Boen, Celso [UNESP]; Goncalves, Joao [UNESP]; Gerig, Guido; Paniagua, Beatriz; IEEE (Ieee, 2018)
Statistical shape analysis captures the geometric properties of a given set of shapes, obtained from medical images, by means of statistical methods. Orthognathic surgery is a type of craniofacial surgery that is aimed at correcting severe skeletal deformities in the mandible and maxilla. Methods assuming spherical topology cannot represent the class of anatomical structures exhibiting complex geometries and topologies, including the mandible. In this paper we propose methodology based on non-rigid deformations of 3D geometries to be applied to objects with thin, complex structures. We are able to accurately and quantitatively characterize bone healing at the osteotomy site as well as condylar remodeling for three orthognathic surgery cases, demonstrating the effectiveness of the proposed methodology.
Keywords: Complex topology; diffeomorphic shape registration; statistical shape modeling; statistical shape analysis; orthognathic surgery